Orbital Influences on Conditions Favorable for Glacial Inception. Issue 21 (3rd November 2021) - O'Neill, Grainne R.; Broccoli, Anthony J.
Abstract: Glacial cycles are driven by cyclical changes in Earth's orbital parameters: obliquity, precession, and eccentricity. A common interpretation of Milankovitch's orbital theory suggests high‐latitude June insolation is the dominant forcing in driving glacial cycles, which places emphasis on the importance of precession. However, there is abundant evidence for the importance of obliquity. Here, we use linear reconstructions based on single‐forcing climate model simulations to produce time series of climate variables important in the growth and decay of ice sheets to examine the relative influences of obliquity and precession in locations important to glacial inception. We show that obliquity can cause changes in positive degree‐days (sum of mean daily temperatures above 0°C) of larger magnitude than those of precession for Scandinavia and Baffin Island. Our positive degree‐day time series were best represented by Milankovitch's caloric summer insolation metric. Snowfall is dominated by obliquity in Scandinavia and by precession in Baffin Island. Plain Language Summary: Earth's climate has varied between periods when ice sheets were confined to polar regions and those when ice was more extensive. Changes in the shape of Earth's orbit and the tilt of its axis were responsible for these variations. Many previous studies have given less emphasis to the effects of changing tilt. Using idealized experiments with a coupled atmosphere‐ocean model, we explored the effects of tilt on conditions favorable for ice sheet growth and retreat. Our results indicate that tilt is important in regions where ice sheet growth first occurred. Key Points: Obliquity influences our melting proxy more strongly than precession in regions of glacial initiation (Scandinavia and Baffin Island) Snowfall is driven by precession in Baffin Island and obliquity in Scandinavia On a larger scale, the relative influence of obliquity and precession depends on climatic quantity and location